DEVELOPMENT MODEL OF BATUR TENGAH VILLAGE AS AN INNOVATIVE VILLAGE WITH A HEALTH PERSPECTIVE BASED ON LOCAL WISDOM - Heri, Mochamad; Agus Ariana, Putu; Yudi Aryawan, Kadek (jfpublisher, 2023)
Introduction. Local economic development implemented by Bangli Regency relies on SME industry clusters on several superior products. One of the efforts to encourage the local economy is to encourage village-level development based on local wisdom, resource potential and uniqueness. Batur Tengah Village was selected as an innovative village. The development of innovative villages is based on the local wisdom of Tri Hita Karana and the policies of the Governor of Bali. This study aimed to design a model for developing a partner village (Batur Tengah Village) as an innovative village based on local wisdom, Higher Education personnel participate and contribute to helping the central government and local governments in breaking the chain of spreading covid-19 at the village level through research and development, Developing business units in the village through dissemination programs of village research results, Designing a model of MBKM activities for students of the Buleleng College of Health Sciences. Methods. Stages of research methods: Designing research, Making research instruments, Determining research locations, research subjects and research objects, Taking research data, Collecting research data, Processing research data, Analyzing research data, Recording research results, Making research discussions, Concluding and making recommendations for research results, Designing innovative village development products/models based on local wisdom, Testing and validating models with expert practitioners, Disseminating products/models. Result & Recommendation. All stakeholder activities is necessary to effectively implement the model. The results of this study also have implications for the need for all Bangli Regency government agencies to align their programs and activities to support an innovative, creative and cultured Central Batur Village based on the Tri Hita Karana concept.